Perceived stigma in fibromyalgia patients and related factors (Annals of Medical Research, 2022)
Aim: Familial and social support is low in fibromyalgia patients. The present study aimed to determine the stigma in fibromyalgia and related factors.Materials and Methods: The study is an observational, descriptive, cross-sectional study. Between May-December 2020, two groups who applied to an outpatient clinic formed the participants: the first group included patients with Fibromyalgia and the second group consists of healthy controls. The presence of stigma was evaluated using the Stigma Scale for Chronic Illnesses. The Multidimensional Scale of Perceived Social Support, The Distress Tolerance Scale, The Discomfort Intolerance Scale, the Fibromyalgia Impact Questionnairev and Visual Analog Scale were used to determine the related factors.Results: In this study, which included 92 fibromyalgia and 46 healthy volunteers , stigma was significantly higher in fibromyalgia patients compared to the healthy controls (p = 0.002). A significant relationship was found between stigma and disease impact (p < 0.001). In addition, as the duration and impact of the disease increased, the stigma scores increased and the rates of social support and resilience decreased (p < 0.001).Conclusion: In fibromyalgia patients, the long duration of the disease, low level of social support, and high disease impact can be counted among the factors associated with stigma.
Keywords: Fibromyalgia; Intolerance; Social support; Stigma